The effect of temperature on consolidation behavior of clay - Tuncan, Muhammet Ahmet. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1984., 1984)
The influence of increasing the temperature in a consolidating soil is examined by consideration of the thermal energy input from the temperature change. This energy provides the potantial necessary to cause flow through physical changes in the pore water, and the soil-water interface. A consolidometer was designed to provide temperature changes through a heating element and the temperatures being measured by a thermostat in the water. The level of temperatures were chosen as: 20°C, 40°C, 60°C, and 80°C. Each temperature level was allowed to remain on the specimen for 24 hours. It was observed that the magnitude of the resulting deformation depended directly on the magnitude of the temperature increase. Void ratio is effected by change in temperature between the range of 20°C to 40°C the most. Changes between the range of 40°C to 60°C, and 60°C to 80°C have, lesser effects respectively. The coefficient of consolidation increases with temperatures in the range of 20°0 to 40°C and 40°C to 60°C, but decreases at temperatures in the range of 60°C to 80°C.
Keywords: Soil consolidation.; Clay soils.